Peningkatan Pengetahuan Kesehatan Gigi dan Mulut Melalui Penyuluhan pada Siswa Madrasah Ibtida’iyah Negeri 2 Bantul: Improving Dental and Oral Health Through Counseling on Students of Madrasah Ibtida’iyah Negeri 2 Bantul - Putri, Saskia Sabrina; Sofiani, Erma (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The importance of maintaining healthy teeth and mouth from an early age through the provision of education is the basis for this community service. The purpose of this activity is to increase knowledge and build habits of elementary school students about maintaining good and correct dental and oral health. The method used in this community service is dental and oral health counseling through audio visuals and demonstrations which are held at Madrasah Ibtida'iyah Negeri (MIN) 2 Bantul. A total of 109 students from grades IV and V were involved in this activity. The activity is accompanied by pre-test and post-test work as well as the practice of brushing teeth together as an indicator of the success of the activity. The results of counseling activities at MIN 2 Bantul showed that there was an increase in knowledge of oral and dental health with higher post-test results of 14% compared to the pre-test and skills in carrying out proper tooth brushing techniques. The conclusion from this activity is that there is an increase in dental and oral health knowledge after providing counseling to students in grades IV and V of Madrasah Ibtida'iyah Negeri (MIN) 2 Bantul.